2009 IEEE International SOC Conference (SOCC) 2009
DOI: 10.1109/soccon.2009.5398015
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive congestion-aware routing algorithm for mesh network-on-chip platform

Abstract: In this paper, an adaptive congestion-aware routing algorithm is proposed for mesh network-onchip (NoC) platforms. Depending on the traffic around the routed node, the proposed routing algorithm provides not only minimum paths but also non-minimum paths for routing packets. Both minimum and non-minimum paths are based on the odd-even turn model to avoid deadlock and livelock problems. The decision of the minimum paths or non-minimum paths depends on the utilities of buffers in neighbor nodes and the specific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Second, an incoming packet cannot be assigned to a buffer that already holds a packet with the same departure time. Additionally, different buffer architectures are also evaluated with different routing algorithms, including XY routing, DyXY [36] and an adaptive routing [37]. Moreover, the proposed data-linked two-level FIFO buffer is implemented using UMC 65 nm standard performance CMOS technology to demonstrate the power consumption and area.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, an incoming packet cannot be assigned to a buffer that already holds a packet with the same departure time. Additionally, different buffer architectures are also evaluated with different routing algorithms, including XY routing, DyXY [36] and an adaptive routing [37]. Moreover, the proposed data-linked two-level FIFO buffer is implemented using UMC 65 nm standard performance CMOS technology to demonstrate the power consumption and area.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…18 presents the average latency under different routing algorithms with the middle buffer and fully associated two-level FIFO buffer architectures. The routing algorithms are XY routing and DyXY [36] routing algorithms and an adaptive congestion-aware routing algorithm [37]. In DyXY and adaptive routing algorithms, the two-level FIFO buffer uses the TDMA arbiter described in Sect.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Recent studies [3], [12], [15] showed that local congestion has a significant impact on network performance. Data transmission between source to destination nodes can suffer with high latency if congestion is encountered.…”
Section: A Congestion and Effects On Noc Performancementioning
confidence: 99%
“…Some algorithms uses multiple information to process congestion. The Path-Congestion Aware Adaptive Routing (PCAR) and an upgraded Odd-Even adaptive routing algorithm both use switch contention along with buffer occupancy levels to route data through a least congested path [18]. Above mentioned techniques are reactive to congestion and only react when it detects on-path congestion.…”
Section: Background and Related Workmentioning
confidence: 99%